2022
DOI: 10.1002/ehf2.13839
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐based estimation of right ventricular ejection fraction

Abstract: Aims A method for estimating right ventricular ejection fraction (RVEF) from RV pressure waveforms was recently validated in an experimental model. Currently, cardiac magnetic resonance imaging (MRI) is the clinical reference standard for measurement of RVEF in pulmonary arterial hypertension (PAH). The present study was designed to test the hypothesis that the pressure-based method can detect clinically significant reductions in RVEF as determined by cardiac MRI in patients with PAH. Methods and results RVEF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…However, no consistent relationship between PH defined as mean PAP of ≥20 mm hg and an RVEF ≤ 45% could be shown in that study. 22 In contrast, Heerdt et al 7,8 showed recently, that pressure-based single beat estimation of RVEF in patients with PH correlated with RVEF measured by MRI. Moreover, in their comparison, they found RVEF as low as 15% with both the single beat method and MRI in the same patients.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…However, no consistent relationship between PH defined as mean PAP of ≥20 mm hg and an RVEF ≤ 45% could be shown in that study. 22 In contrast, Heerdt et al 7,8 showed recently, that pressure-based single beat estimation of RVEF in patients with PH correlated with RVEF measured by MRI. Moreover, in their comparison, they found RVEF as low as 15% with both the single beat method and MRI in the same patients.…”
Section: Discussionmentioning
confidence: 95%
“…The novel single‐beat pressure approach for the calculation of RVEF has been validated by cardiac MRI in two studies with 31 patients suffering from PH or heart failure with preserved ejection fraction. 7 , 8 For the calculation of Tau, we used the logistic approach as evaluated and proposed by Ogilvie et al 10 We tested the reliability of our algorithms by manual evaluation of both RVEF and Tau, showing excellent correlation with automated calculation by our written software.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations